Deskripsi Kesalahan Pengoperasian Bentuk Aljabar Berdasarkan Gaya Belajar Auditorial - Hamid, Abdurrahman; Asmaun, Asmaun; Rahman, Muhammad Syarifuddin (Universitas Cokroaminoto Palopo, 2025)
The present research is a descriptive study employing a qualitative technique, aimed at elucidating the misconceptions regarding the operation of algebraic expressions based on auditory learning styles. This study aims to discover and examine the misconceptions encountered by students with auditory learning styles in comprehending mathematical ideas. The participants in this study were eighth-grade students from class VIII-A of a junior high school with an auditory learning style. The data's validity in this study was established by temporal triangulation procedures to assure the consistency and reliability of the findings. The study utilized a learning style assessment to evaluate students' preferences and a concept comprehension test using a Confidence Rating Index (CRI) to thoroughly identify students' misconceptions. The study's results showed that the research subjects coded YTA experienced various misconceptions about classifying objects according to certain properties according to their concepts, simplifying algebraic forms in various forms of mathematical representation, using and utilizing and selecting certain procedures or operations, and applying concepts or algorithms in problem solving. In addition, the subjects also experienced obstacles in applying concepts or algorithms to solve mathematical problems systematically. According to these findings, students' conceptual understanding of algebraic topics may be influenced by their auditory learning styles, particularly when integrating auditory representations with symbolic notions. Consequently, enhanced adaptive learning tactics are required, including the utilization of audio media to assist students with auditorial learning preferences in comprehending mathematical concepts more effectively and reducing the likelihood of misconceptions